Professional Leadership of School Principals in Improving the Effectiveness of Islamic Education Management - Ade Susrianti; Aini Gustia; Nur Hadana Afifah; Syafaatul Habib; Khrisfison (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to examine the role of professional school leadership in enhancing the effectiveness of Islamic education management. Professional leadership includes the ability to plan, organize, implement, and evaluate educational programs in line with Islamic values. In this context, the principal functions not only as an administrative manager but also as a spiritual leader and motivator capable of fostering a morally sound and conducive educational environment. This research uses a descriptive qualitative method with data collected through observation, interviews, and documentation. The results show that the professional leadership of school principals positively influences the effectiveness of Islamic education management, particularly in human resource management, improving the quality of learning, and building a religious school culture.